1998
DOI: 10.1128/iai.66.6.2666-2673.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Fibrinogen-Binding Protein of Staphylococcus epidermidis

Abstract: The present study reports on fibrinogen (Fg) binding ofStaphylococcus epidermidis. Adhesion of differentS. epidermidis strains to immobilized Fg was found to vary significantly between different strains, and the component responsible was found to be proteinaceous in nature. To further characterize the Fg-binding activity, a shotgun phage display library covering the S. epidermidis chromosome was constructed. By affinity selection (panning) against immobilized Fg, a phagemid clone, pSEFG1, was isolated, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
97
0
5

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(103 citation statements)
references
References 33 publications
1
97
0
5
Order By: Relevance
“…S. epidermidis produces surface proteins that are involved in the interaction with host proteins of the extracellular matrix present in the host-derived conditioning film, and therefore in biofilm formation (von Eiff et al 2002). Examples include the surface associated autolysin AtlE , which promotes binding to polystyrene surfaces and is also involved in vitronectin adhesion, the fibrinogen-binding Fbe (Nilsson et al 1998) and SdrG, SdrF and SdrH cell-surface-associated proteins (McCrea et al 2000). Fbe, SdrG, SdrF and SdrH are all members of the recently identified protein family, the serine-aspartate (SD)-repeat-containing (Sdr) family of cellwall-anchored surface proteins (von Eiff et al 2002), which interact with extracellular matrix proteins.…”
Section: Attachment To Biotic Surfacesmentioning
confidence: 99%
“…S. epidermidis produces surface proteins that are involved in the interaction with host proteins of the extracellular matrix present in the host-derived conditioning film, and therefore in biofilm formation (von Eiff et al 2002). Examples include the surface associated autolysin AtlE , which promotes binding to polystyrene surfaces and is also involved in vitronectin adhesion, the fibrinogen-binding Fbe (Nilsson et al 1998) and SdrG, SdrF and SdrH cell-surface-associated proteins (McCrea et al 2000). Fbe, SdrG, SdrF and SdrH are all members of the recently identified protein family, the serine-aspartate (SD)-repeat-containing (Sdr) family of cellwall-anchored surface proteins (von Eiff et al 2002), which interact with extracellular matrix proteins.…”
Section: Attachment To Biotic Surfacesmentioning
confidence: 99%
“…Other adhesin genes described in S. epidermidis clinical isolates, such as the atIE gene and the fbe gene (Nilsson et al, 1998) are present in ATCC 12228. Recently, an extracellular-matrix-binding protein Embp has been identified as the fibronectin binding protein of Staphylococcus epidermidis in strain NCTC 11047 (Williams et al, 2002), and this protein is also found in Staphylococcus aureus (Hussain et al, 2001).…”
Section: Pathogenicity Factorsmentioning
confidence: 99%
“…Casein, human serum albumin (HSA) and human fibronectin were from Sigma, and human fibrinogen was from IMCO Corp. Ltd. (Stockholm, Sweden). The fibrinogen-binding part (amino acids 52-646) of protein Fbe [14] of Staphylococcus epidermidis was expressed in E. coli following the same general scheme as described below under Section 2.5.…”
Section: Proteins and Reagentsmentioning
confidence: 99%